Genetic variants of the CYP1B1 gene as predictors of biochemical recurrence after radical prostatectomy in localized prostate cancer patients. Issue 27 (July 2016) - Gu, Cheng-Yuan; Qin, Xiao-Jian; Qu, Yuan-Yuan; Zhu, Yu; Wan, Fang-Ning; Zhang, Gui-Ming; Sun, Li-Jiang; Zhu, Yao; Ye, Ding-Wei
Abstract : Abstract: Clinically localized prostate cancer is curative. Nevertheless many patients suffered from biochemical recurrence (BCR) after radical prostatectomy (RP). Mounting evidence suggest that estrogen and xenobiotic carcinogens play an essential role in progression of prostate cancervia oxidative estrogen metabolism. CYP1B1 is an enzyme involved in the hydroxylation of estrogens, a reaction of key relevance in estrogen metabolism. Given the role of CYP1B1 in the oxidative metabolism of endogenous/exogenous estrogen and compounds, CYP1B1 polymorphisms have the potential to modify its expression and subsequently lead to progression. We hypothesize that genetic variants of the CYP1B1 gene may influence clinical outcome in clinically localized prostate cancer patients. In this cohort study, we genotyped 9 tagging single nucleotide polymorphisms (SNPs) from the CYP1B1 gene in 312 patients treated with RP. For replication, these SNPs were genotyped in an independent cohort of 426 patients. The expression level of CYP1B1 in the adjacent normal prostate tissues was quantified by reverse transcription and real-time polymerase chain reaction. Kaplan–Meier analysis and Cox proportional hazard models were utilized to identify SNPs that correlated with BCR. CYP1B1 rs1056836 was significantly associated with BCR (hazard ratio [HR]: 0.69; 95% confidence interval [CI]: 0.40–0.89, P = 0.002) and relative CYP1B1 mRNA expression. Our findings suggest inherited genetic variation in the CYP1B1 gene may contribute to variable clinical outcomes for patients with clinically localized prostate cancer. Abstract : Supplemental Digital Content is available in the text